THE CURRENT STATE OF THE PROBLEM OF CHILDREN HEALTH BORN IN RESULT OF THE ASSISTED REPRODUCTIVE TECHNOLOGIES - V.O. Mansimova (Педиатрическая фармакология)
A brief historical background of development of the assisted reproductive technologies (ART) is presented. The works of russian and foreign authors about the neonatal period, the health of babies born in result of different methods of ART (in vitro fertilization using ICSI) were analyzed. After discussion there were indicated new approaches for prevention of perinatal morbidity and ensuring harmonious development and quality of life for these children. The necessity of a national multicenter study of the status of children born in result of induced pregnancy was proved.Key words: assisted reproductive technologies, IVF, ICSI technique, newborns, health.